2002
DOI: 10.1021/jp013153x
|View full text |Cite
|
Sign up to set email alerts
|

Conditions of Formation of Copper Phyllosilicates in Silica-Supported Copper Catalysts Prepared by Selective Adsorption

Abstract: It is shown that, during the preparation of Cu/SiO 2 samples by selective adsorption of copper tetraammine complex [Cu(NH 3 ) 4 (H 2 O) 2 ] 2+ on silica, two types of supported Cu II species form: grafted Cu II ions and copper phyllosilicate. The formation of grafted Cu II ions results from electrostatic adsorption of Cu II ammine complex cations in solution onto the surface of silica particles negatively charged due to the high solution pH. Grafting of Cu II ions occurs during the subsequent drying step. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
140
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(154 citation statements)
references
References 40 publications
10
140
0
Order By: Relevance
“…Finally, when comparing the average pore size of the materials, a significant increase can be recognized for the ADP sample. This seems to originate from the dissolution of the silica's outer layer in the pore, accomplished by the high solution pH (≈11) of the ADP method [27]. Despite the significant loss in surface area and pore size increase due to this dissolution under basic conditions, the pore shape of the ADP sample remains intact with a pore volume comparable to that of the MDD sample.…”
Section: Textural Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, when comparing the average pore size of the materials, a significant increase can be recognized for the ADP sample. This seems to originate from the dissolution of the silica's outer layer in the pore, accomplished by the high solution pH (≈11) of the ADP method [27]. Despite the significant loss in surface area and pore size increase due to this dissolution under basic conditions, the pore shape of the ADP sample remains intact with a pore volume comparable to that of the MDD sample.…”
Section: Textural Propertiesmentioning
confidence: 99%
“…The peak at a lower binding energy (BE) is attributed to the CuO species distributed on the surface, while the peak at a higher BE can be due to the formation of copper hydroxyl groups or to the interaction with the neighboring Si-O bonds. Toupance et al reported the existence of two types of well-dispersed Cu 2+ species when using the ammonia-based method for metal impregnation, i.e., copper phyllosilicate and grafted Cu 2+ [27]. Copper phyllosilicate has a lamellar structure wherein the layers of SiO4 tetrahedra are sandwiched between discontinuous layers of CuO6 octahedra [27,32].…”
Section: Copper Oxide Dispersionmentioning
confidence: 99%
See 3 more Smart Citations